Characterization of Asymptomatic Bacteriuria Escherichia coli Isolates in Search of Alternative Strains for Efficient Bacterial Interference against Uropathogens - Stork, Christoph; Kovács, Beáta; Rózsai, Barnabás; Putze, Johannes; Kiel, Matthias; Dorn, Ágnes; Kovács, Judit; Melegh, Szilvia; Leimbach, Andreas; Kovács, Tamás; Schneider, György; Kerényi, Monika; et al. (Frontiers in Microbiology, 2018)
Asymptomatic bacterial colonization of the urinary bladder (asymptomatic bacteriuria, ABU) can prevent bladder colonization by uropathogens and thus symptomatic urinary tract infection (UTI). Deliberate bladder colonization with E.coli ABU isolate 83972 has been shown to outcompete uropathogens and prevent symptomatic UTI by bacterial interference. Many ABU isolates evolved from uropathogenic ancestors and, although attenuated, may still be able to express virulence-associated factors. Our aim was to screen for efficient and safe candidate strains that could be used as alternatives to E.coli 83972 for preventive and therapeutic bladder colonization. To identify ABU E.coli strains with minimal virulence potential but maximal interference efficiency, we compared nine ABU isolates from diabetic patients regarding their virulence- and fitness-associated phenotypes in vitro, their virulence in a murine model of sepsis and their genome content. We identified strains in competitive growth experiments, which successfully interfere with colonization of ABU isolate 83972 or uropathogenic E.coli strain 536. Six isolates were able to outcompete E.coli 83972 and two of them also outcompeted UPEC 536 during growth in urine. Superior competitiveness was not simply a result of better growth abilities in urine, but seems also to involve expression of antagonistic factors. Competitiveness in urine did not correlate with the prevalence of determinants coding for adhesins, iron uptake, toxins, and antagonistic factors. Three ABU strains (isolates 61, 106 and 123) with superior competitiveness relative to ABU model strain 83972 display low in vivo virulence in a murine sepsis model, and susceptibility to antibiotics. They belong to different phylogroups and differ in the presence of ExPEC virulence- and fitness-associated genes. Importantly, they all lack marked cytotoxic activity and exhibit a high LD50 value in the sepsis model. These strains represent promising candidates for a more detailed assessment of relevant fitness traits in urine and their suitability for therapeutic bladder colonization.